1991
DOI: 10.1346/ccmn.1991.0390204
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Iron Oxidation State on the Texture and Structural Order of Na-Nontronite Gels

Abstract: --Aqueous gels of unaltered (oxidized) and chemically reduced ferrnginous smectite (SWa-1 from the Source Clays Repository of The Clay Minerals Society) were characterized by transmission electron microscopy, electron diffraction, and energy-dispersive X-ray fluorescence to establish details regarding their texture, inter-layer and inter-particle arrangements, and chemical composition. Micrographs revealed that the reduction of structural Fe(III) to Fe(II) caused a consolidation of smectite particles from an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
51
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 22 publications
7
51
0
Order By: Relevance
“…The effect of oxidation state on bulk density is understandable in light of earlier studies which revealed that Fe reduction decreases the water content of the clay at a given applied pressure (Stucki et al, 1984c), decreases the specific surface area (Lear and Stucki, 1989), and increases the particle size (Stucki and Tessier, 1991). The reduction of structural Fe(III) to Fe(II) consolidates smectite particles from an extensive network of small crystals (1-6 layers thick) to distinct particles of limited size in the a-b direction and about 20-40 layers thick (Stucki and Tessier, 1991).…”
Section: In-suspension Experimentsmentioning
confidence: 94%
See 2 more Smart Citations
“…The effect of oxidation state on bulk density is understandable in light of earlier studies which revealed that Fe reduction decreases the water content of the clay at a given applied pressure (Stucki et al, 1984c), decreases the specific surface area (Lear and Stucki, 1989), and increases the particle size (Stucki and Tessier, 1991). The reduction of structural Fe(III) to Fe(II) consolidates smectite particles from an extensive network of small crystals (1-6 layers thick) to distinct particles of limited size in the a-b direction and about 20-40 layers thick (Stucki and Tessier, 1991).…”
Section: In-suspension Experimentsmentioning
confidence: 94%
“…The reduction of structural Fe(III) to Fe(II) consolidates smectite particles from an extensive network of small crystals (1-6 layers thick) to distinct particles of limited size in the a-b direction and about 20-40 layers thick (Stucki and Tessier, 1991). The stacking of layers is also more ordered when the clay is reduced.…”
Section: In-suspension Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…A typical native bentonite, such as the widely studied Wyoming Bentonite MX-80, consists of nearly 3 wt% Fe, the major part being structural Fe(III) replacing Al 3+ in the aluminum octahedral sheet [3]. At elevated Fe(II)/Fe Tot ratios however, significant changes in several physical properties such as the swelling pressure, cation exchange capacity (CEC), total layer charge, specific surface area as well as microstructural properties has been found in previous studies [4][5][6][7][8][9]. After the initial saturation of the bentonite barrier, anoxic conditions are expected.…”
Section: Introductionmentioning
confidence: 99%
“…The redox state of the clay and knowledge of how to control or exploit it are of great importance to agriculture, industry, and the environment because of their profound effects on many physical-chemical properties of the clay Lear and Stucki, 1989;Komadel et al, 1990;Khaled and Stucki, 1991;Stucki and Tessier, 1991).…”
Section: Introductionmentioning
confidence: 99%